Art of Makeup as a Visual Medium - Kusumadinata, Ali Alamsyah; Chaniago, Novira Faradila; Hasbiyah, Desi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Makeup art is a form of face painting that highlights handmade skills. It shows one's ability to develop artistic character, especially in the visual aspect. This ability is honed through practice and the application of concepts inspired by face shapes. Makeup skills are based on an understanding of personality which is mainly reflected in an attractive and regular appearance. This not only increases self-confidence but also helps build good relationships and has a positive impact on individuals who use makeup. This study aims to describe the views of facial stylists on visual elements. A qualitative approach is used in this research method, by building constructions based on the statements provided. Field data is combined with theory, especially in the context of visual communication which is based on graphic elements. The results showed that a line is a series of points used in various contexts. Form is a symbolization formed by lines or combinations of lines with other elements. Color plays an important role in creating separation, emphasis, and harmony in works of art. Color psychology suggests that each color has certain emotional effects, ranging from positive to negative. It is believed to have a great influence on emotions, psychology, and human behavior, so it can communicate non-verbally and convey messages with deep meaning.